Searching for sectoral patterns of innovation in european manufacturing industry - Varum, C. A. (2012)
The present paper is conducted under the research project “Enterprise of the Future: Trends and Scenarios towards Competitiveness” which attempts to disclosure determinants of future enterprise competitiveness. Innovation is not only a must today but also an imperative in future competitiveness scenarios. In modern evolutionary economics it is argued that sector-specific factors are one of the key factors explaining innovative behaviour and performance of firms. Several contributions have pointed that industries largely differ in terms of knowledge base and technological sources, opportunities and appropriation of innovative activities, technological trajectories and firms’ strategies. Using as background Pavitt’s taxonomy, this paper explores the nature, extent and sources of variety of innovation in the manufacturing industry, aiming at identifying common patterns across industries, and sectoral patterns across countries. This paper presents evidence based on the aggregated results of the last IV Community Innovation Survey released by EUROSTAT (CIS4), for which data is available for a number of industries and countries.